Patterns and Correlates of New Drug Initiation among Female Exotic Dancers: The Contribution of Occupational and Structural Risks. (15th April 2020) - Rosen, Joseph G.; Park, Ju Nyeong; Opper, Neisha; Lim, Sahnah; Sherman, Susan G.
Abstract: Introduction: Exotic dance clubs (EDCs) can play pivotal roles in the production of drug-related risks for female exotic dancers (FED). We aimed to characterize the structural and occupational factors associated with new drug initiation post-EDC entry among new FED ( N  = 117) in Baltimore, Maryland. Materials and Methods: Logistic regression models tested the associations of new drug uptake, measured as initiating any illicit drug (including non-prescribed and diverted prescription narcotics) not used prior to EDC employment, with structural (e.g. debt sources, housing instability) and occupational (e.g. sex work, dancing as sole income source) vulnerabilities. Results: Most FED were younger than 24 years-old (60%), identified as Black/African American (61%), and did not complete high school (56%). Twenty-nine (25%) reported using any new drug post-EDC entry, with cocaine (34%) cited most frequently among newly initiated substances. In multivariable analysis, drug initiation was significantly associated with cumulative debt sources (Adjusted Odds Ratio [AOR] = 1.82, 95% Confidence Interval [CI]: 1.19–2.77), dancing as only income source (AOR = 4.21, CI: 1.29–13.71), and sex work (AOR = 9.26, CI: 2.74–31.32). Conclusions: Our findings implicate co-occurring structural and occupational factors in FED's initiation of illicit drugs proceeding EDC employment. Results demonstrate the coping role of drug use for FED in stressful working environments and the multiple vulnerabilities associated with illicit drug uptake. The study reinforces a need for harm reduction interventions (i.e. debt relief, employment connections, increased hourly pay) that consider the contribution of overlapping financial insecurities to the production of occupational risks motivating drug uptake.